Geometric Shapes Media for Cognitive Abilities in Early Childhood: Media Bentuk Geometri untuk Kemampuan Kognitif Anak Usia Dini - Umyati; IFFATUR ROCMAH, LULUK (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Cognitive development in early childhood is a critical foundation for later learning and problem-solving skills. Specific Background: Many children at the age of 4–5 years still experience difficulties in recognizing and classifying geometric shapes, which hinders their logical thinking ability. Knowledge Gap: Previous studies have explored learning media for early childhood, but limited evidence exists on the direct role of geometric shape media in stimulating cognitive growth. Aims: This study aims to examine how geometric shape media can improve the cognitive abilities of children aged 4–5 years in IT Nurul Hidayah Kindergarten. Results: Using a pre-experimental design (one-group pretest–posttest) with 36 participants, the findings show a significant increase in posttest scores compared to pretest (mean score rising from 58.05 to 86.11). Statistical analysis confirmed significance with Tcount = 38.65 > Ttable = 1.691. Novelty: This research highlights the application of simple, tangible, and context-related geometric media that directly engage children in learning through play. Implications: The results suggest that integrating geometric shape media into early childhood learning environments can effectively foster logical reasoning and classification skills crucial for cognitive development.Hightlights: Geometric media significantly improve children’s cognitive abilities. Novel use of tangible, play-based materials for early learning. Supports practical integration into PAUD learning environments. Keywords: Early Childhood Education; Cognitive Development; Geometry; Learning Media;